Factors affecting average processing time in retail banking services. - Mohamad Karim Mohamad Isa (2017)
This research explores the factors affecting average processing time in retail banking services. In doing so, the research aims to address the rooms of improvement that can be made to further improve the achievement of Queue Management System (QMS),particularly in Public Bank Kota Bharu Branch, in addition to providing an analysis of factors affecting the increase in processing time, which has implications for the QMS performance. The purpose of this study to establish the relationship between the factors of Gender, Age, Number of transaction and number of customer served toward average processing time among tellers in Public Bank Berhad, Kota Bharu Branch, Malaysia. The finding revealed that the four dimensions of gender, age, number of transaction and number of customer served have no significant positive effect on average processing time. Thus, all the factors in the study revealed that there is no relationship between the factor discussed and other constant of factors may be included in future research.